Perpanjangan Sertifikat Keselamatan Kapal Ahts. PASIFIC BRONZE pada Kantor Kesyahbandaran dan Otoritas Pelabuhan (KSOP) Khusus Batam oleh PT. Pelayaran Siltor Adimulia Batam - Wasinton B. Hutagaol; Dirhamsyah Dirhamsyah; Fadiyah Hani Sabila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Pelayaran Siltor Adimulia which operates in the field of Ship Agency Services, which has served many domestic and foreign ships, PT. Siltor Adimulia Shipping has a combination of knowledge of the shipping industry and Marine services with experienced staff, and always provides needs with satisfaction. Operational department of PT. Siltor Adimulia Shipping will take care of all the needs and requirements for extending the ship's safety certificate. The results of the research regarding ship safety certificate extension services, the agent's role is to prepare everything in the procedures for extending ship safety certificates until a new certificate is issued. The activity for extending the ship's safety certificate went quite well but was less than optimal, due to a lack of coordination between the ship and the Marine Inspector who came to the ship during the inspection. For the stages of extending the AHTS ship safety certificate. PACIFIC BRONZE at PT. Sailing Siltor Adimulia Batam on the Batam Special KSOP is more optimal, it is recommended to increase good cooperation and time coordination to improve communication channels between the ship and the Marine Inspector when they want to carry out this work.